Performance-based design of strip foundation considering the full effect of ground improvement - Yu, Yang; Mao, Xufei; Shen, Mengfen (Journal of Civil Engineering and Management, 2024)
Ground improvement is an effective way to improve the bearing capacity of a shallow foundation. However, the benefit of reducing uncertainties in soil parameters for shallow foundation design is rarely recognized. This study investigated the full effect of rapid impact compaction (RIC) on a strip foundation design. The finite difference method coupled Monte Carlo simulation were used to calculate the failure probability and the required width of the strip foundation, where the friction angle of soil was treated as a random variable. The results show that the foundation width reduces by 48.5% when considering the full effect of RIC, and a significant part of the reduction came from the decrease in the uncertainty of friction angle. Although the adopted relationship between the friction angle and tip resistance of cone penetration test affects the designed width of the foundation, the full effect of ground improvement contributed by the uncertainty reduction of soil parameters is still significant. The implication of the present study provides a basis for the performance-based bearing capacity design of shallow foundations.